External Sector Dynamics in India: The Role of Trade Policy and Capital Inflows - Naidu, P.A.; Singh, Anurag Vikram (Indonesian Journal Publisher, 2026)
This study examines the long-run dynamics of India’s trade balance over the period 1960–2022 using a qualitative and graphical time-series approach. The analysis focuses on trade balance as a percentage of GDP and its structural relationship with exports, imports, foreign direct investment (FDI), tariff rates, and annual tariff changes. Through trend analysis and graphical interpretation, the study identifies major regime shifts associated with trade liberalization and economic reforms, particularly after 1991.The findings indicate that India has experienced persistent trade deficits throughout most of the sample period. Although export intensity increased significantly following liberalization, import growth often outpaced exports, contributing to widening deficits during high-growth phases. The sharp decline in tariff rates and rising FDI inflows reflect increasing global integration, but these developments have also been associated with greater external vulnerability. The study highlights the structural transformation of India’s external sector and underscores the macroeconomic and policy factors shaping its trade balance dynamics.